Reflective practice tools in ESL: Two retrospective evaluations - Unlu, Zuleyha; Kulekci, Erkan (Walter de Gruyter GmbH, 2018)
Abstract This article evaluates the use of reflective practice (RP) tools by focusing on the main critiques on RP. In the literature, RP has often been criticised for its design-related problems, RP’s being directed by problem identification purposes rather than empirical data, and RP practitioners’ loss of contact with their discourse communities due to the undue emphasis on practical knowledge. Therefore, this article suggests methodological and data triangulation of RP tools as well as highlighting the community of inquiry framework to overcome the aforementioned problems While doing this, the authors reflect on their own RPs, both of which were conducted at a refugee centre in Philadelphia, USA. In this examination, the critical role of reflective tools is highlighted.